Vaccine procurement during an influenza pandemic and the role of Advance Purchase Agreements: Lessons from 2009-H1N1. Issue 3 (15th March 2016) - Turner, Mark
Abstract : Vaccines are hugely important tools in minimising the effect pandemic influenza could have on a population. The reforms introduced by the Pandemic Influenza Preparedness Framework are ill-suited to providing sufficient levels of access to vaccines to meet the needs of developing states, and as such developing states will continue to be reliant upon the traditional methods of vaccine procurement to procure the majority of the vaccines they required. Using procurement during 2009-H1N1 as a case study, this paper examines the methods of procurement utilised by states in order to determine if the procurement tools available to developing states are sufficient to procure adequate levels of pandemic influenza vaccines. Particular focus is given to the role Advance Purchase Agreements (APAs) play in the procurement process. By exploring this case study it is possible to argue that these procurement methods are ineffective for developing states, and when the next influenza pandemic occurs, demand will once again outstrip supply globally, due to supply of vaccines being dominated by the developed states with APAs in place.